Pelatihan Digital Marketing Untuk Meningkatkan Pemasaran Desa Wisata Di Desa Abu Sakim Kabupaten Bengkulu Tengah - Marsa, Selvin; Syapriludin, Syapriludin (Universitas Dehasen Bengkulu, 2021)
Training in digital marketing is increasingly recognized as key to increasing tourism visibility and attractiveness, particularly in rural tourism destinations. This study aims to evaluate the effectiveness of digital marketing training in improving the marketing of Desa Wisata in Abu Sakim Village, Central Bengkulu Regency. Using both quantitative and qualitative approaches, data was collected through surveys and interviews with tourism-related stakeholders in the village. Results showed that the digital marketing training significantly improved the understanding of digital marketing strategies and the use of social media platforms among tourism business owners. In addition, participants also reported an increase in the number of visitors and revenue after implementing the marketing strategies learned during the training. The implications of this study highlight the importance of digital marketing training as a means to strengthen the local economy and increase tourism attractiveness in rural destinations.